Plantation-driven deforestation and ecosystem degradation: Assessing the efficacy of environmental governance in tropical forest landscapes - Yosua Partahian Siahaan (Jurnal Bisnis Kehutanan dan Lingkungan, 2026)
Background: Plantation expansion has emerged as a major catalyst of land-use transformation across tropical regions, including Bulungan Regency, North Kalimantan, where extensive deforestation and ecosystem degradation have occurred over the last two decades. This research investigates the interlinkages between plantation growth, deforestation, and environmental decline to construct a holistic understanding of ecological changes in plantation-dominated landscapes. While prior research indicates that uncontrolled development of oil palm and rubber plantations has driven deforestation, biodiversity loss, and greenhouse gas (GHG) emissions, spatially detailed assessments at the regional level remain scarce. Method: Employing a descriptive–quantitative approach, this study utilizes secondary spatial and temporal datasets from Global Forest Watch and the Central Bureau of Statistics (2001–2024) to evaluate changes in forest cover, tree loss caused by fire, and GHG emission trends. Finding: Integrated spatial-statistical analyses reveal that Regency has lost approximately 197,000 hectares of primary moist forest (19% of its total), with about 69% of tree cover loss driven by permanent land-use conversion linked to plantation expansion. Fires contributed 6.8% of total tree loss and were spatially associated with recently established plantations. GHG emissions peaked at 19.8 MtCO₂e in 2012, aligning with a period of intensive deforestation, but declined to 5.52 MtCO₂e in 2024 due to enhanced environmental governance. Conclusion: The findings indicate that plantation-induced land conversion alters hydrological processes, reduces atmospheric humidity, and accelerates carbon emissions, forming a feedback loop that amplifies regional climate effects. This study contributes an integrated spatial perspective on plantation-driven deforestation and its ecological implications, offering new insights for sustainable land-use management in tropical regions. Novelty/Originality of this article: This study provides a long-term (24-year) spatio-temporal analysis that specifically identifies the "feedback loop" between plantation-driven deforestation, localized fire susceptibility, and GHG emission fluctuations.